The Impact of COVID-19 on Distress Tolerance in Pakistani Men and Women - Shahzad, Salman; Kliewer, Wendy; Bano, Nasreen; Begum, Nasreen; Ali, Zulfiqar (Frontiers in Psychology, 2022)
The novel coronavirus (COVID-19) is an infectious disease that spread across the world, bringing with it serious mental health problems for men and women. Women in Pakistan are infected with COVID-19 at a much lower rate than men, yet report worse mental health. To explain this paradox, we surveyed 190 participants (46% male) shortly following the country lockdown, focusing on perceptions of the COVID-19 impact and positive adjustment. Measures used in this study included the Warwick-Edinburgh Mental Well-being Scale and Distress Tolerance Scale. Factor analysis revealed five distinct areas related to COVID-19, which did not differ by sex. However, men reported higher levels of both distress tolerance and well-being than women. High endorsement of actions to protect against COVID-19 was related to lower distress tolerance scores, but in different ways for men and women. Men, but not women, who endorsed more protective measures to stop the pandemic reported higher DTS absorption scores, and therefore being more consumed by distress; women who endorsed more protective measures to stop the pandemic reported less acceptance of distress than men, as reflected in DTS appraisal scores. An in-depth analysis of women’s beliefs and behaviors related to COVID-19 is warranted to understand why Pakistani women who are infected with COVID-19 at lower rates than men show more mental health symptoms.